PENGARUH SISTEM INFORMASI AKUNTANSI PADA KINERJA KEUANGAN DENGAN SISTEM PENGENDALIAN INTERNAL SEBAGAI VARIABEL PEMODERASI - Mulyatini, Ni Wayan; Widanaputra, A.A.G.P.; Putri, I.G.A.M. Asri Dwija; Ratna Sari, Maria Mediatrix (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
Public sector accounting practices carried out by government institutions have received much attention compared to the previous period. There is a greater demand from the public for the implementation of transparency and public accountability by public sector institutions. The purpose of this study was to analyze the internal control system in moderating the influence of accounting information systems on financial performance in Badung Regency. This research was conducted in Badung Regency using primary data obtained from questionnaires. The method of determining the sample using the saturated method with 60 respondents obtained. The data analysis technique used is the interaction test of moderated regression analysis (MRA) variables. The results of the analysis show that the clearer the accounting information system, the higher the financial performance moderated by the internal control system in Badung Regency. The implications of this research include two things, namely theoretical implications and practical implications. Theoretical implications relate to the contribution of this research to goal setting theory related to accounting information systems, internal control systems and financial performance. The practical implications relate to the contribution of research to improving financial performance in Badung Regency.